A arte do circo como mediadora na constituição do sujeito e na ampliação de suas possibilidades - Silva, Daniel vieira da (2023)
This research aimed to reflect on the theme that involves art, training and artistic experiences within the circus context. The study problem was based on the questioning of how art can be a powerful instrument of mediation in the constitution of the subject. The methodology used was bibliographic research in works that value both classical and recent theorists, in addition to field research that intended to value the subjective constructions that guide this process. In order to carry out the field research, we contacted four subjects who experienced training processes in a circus school and who currently define themselves as artists, art educators and teachers in the circus area. Through interviews, we obtained information about how these subjects experience their aesthetic processes and how the context of teaching circus art was conceived as an expander of possibilities professional and artistic.